The Type I superluminous supernova catalogue – II. Spectroscopic evolution in the photospheric phase, velocity measurements, and constraints on diversity - Aamer, Aysha; Nicholl, Matt; Gomez, Sebastian; Berger, Edo; Blanchard, Peter; Anderson, Joseph P.; Angus, Charlotte; Aryan, Amar; Ashall, Chris; Chen, Ting-Wan; Dimitriadis, Georgios; Galbany, Lluis; et al. (Oxford University Press (OUP), 2026)
Hydrogen-poor superluminous supernovae (SLSNe) are among the most energetic explosions in the universe, reaching luminosities up to 100 times greater than those of normal supernovae. This paper presents the largest compilation of SLSN photospheric spectra to date, encompassing data from the advanced Public ESO Spectroscopic Survey of Transient Objects (ePESSTO+), the Finding Luminous and Exotic Extragalactic Transients (FLEET) search, and all published spectra up to December 2022. The data set includes a total of 974 spectra of 234 SLSNe. By constructing average phase binned spectra, we find SLSNe initially exhibit high temperatures (10 000−11 000 K), with blue continua and weak lines. A rapid transformation follows, as temperatures drop to 5000−6000 K by 40 d post-peak, leading to stronger P-Cygni features. Variance within the data set is slightly reduced when defining the phase of spectra relative to explosion, rather than peak, and normalising to the population’s median e-folding decline time. Principal Component Analysis (PCA) supports this, requiring fewer components to explain the same level of variation when binning data by scaled days from explosion, suggesting a more homogeneous grouping. Using PCA and K-means clustering, we identify outlying objects with unusual spectroscopic evolution and evidence for energy input from interaction, but find no support for groupings of two or more statistically significant subpopulations. We find Fe II λ5169 line velocities closely track the radius implied from blackbody fits, indicating formation near the photosphere. We also confirm a correlation between velocity and velocity gradient, which can be explained if all SLSNe are in homologous expansion but with different scale velocities. This behaviour aligns with expectations for an internal powering mechanism.